Adhesives, sealants, and coatings for the electronics industry - Flick, Ernest W. (Noyes Publications, 1992)
Contains descriptions of more than 2,500 adhesives, sealants, and coatings, which are available to the electronics and related industries. Compiled from information received from 80 manufacturers and distributors of these products. The data, including product specifications, represent selections from the manufacturers' descriptions.